2018
DOI: 10.3389/fimmu.2018.00808
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein as a Therapeutic Target in Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD), a retinal degenerative disease, is the leading cause of central vision loss among the elderly population in developed countries and an increasing global burden. The major risk is aging, compounded by other environmental factors and association with genetic variants for risk of progression. Although the etiology of AMD is not yet clearly understood, several pathogenic pathways have been proposed, including dysfunction of the retinal pigment epithelium, inflammation, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 92 publications
0
29
0
Order By: Relevance
“…The prognostic impact of CRP shows that the acute phase reaction is important in renal cell carcinoma [ 39 , 58 , 59 , 60 ]. CRP is not only a marker but also a mediator with distinct biological functions [ 61 , 62 , 63 ]. However, the systemic acute phase reaction is a very complex response, and the aim of our present study was, therefore, to investigate the systemic levels of acute phase cytokines in renal cancer patients with a focus on the acute phase cytokine profiles, rather than those of single cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic impact of CRP shows that the acute phase reaction is important in renal cell carcinoma [ 39 , 58 , 59 , 60 ]. CRP is not only a marker but also a mediator with distinct biological functions [ 61 , 62 , 63 ]. However, the systemic acute phase reaction is a very complex response, and the aim of our present study was, therefore, to investigate the systemic levels of acute phase cytokines in renal cancer patients with a focus on the acute phase cytokine profiles, rather than those of single cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, monomeric-CRP has shown to induce an inflammatory phenotype ( 50 ) and blood–retinal barrier disruption in RPE cells ( 51 ). Given the similarities of risk factors between CVD and AMD, this approach could be considered as a local adjuvant therapy in future new strategies for patients at greater risk, such as women with high CRP levels and at-risk A69S genotype ( 52 ). This could contribute to a better quality of life and reduce personal burden for AMD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a plausible scenario would infer that, in the presence of an already aged/damaged RPE, mCRP reaches the apical side of the RPE to amplify the proinflammatory microenvironment and enhance barrier disruption. With respect to previous findings, this pathologic mechanism will be more prevalent in patients carrying the FH risk polymorphism for AMD, where mCRP proinflammatory effects remain unrestrained [28].…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, we also showed that the “non-risk” Factor H (FH) variant can effectively bind to mCRP to dampen mCRP pro-inflammatory activity [ 27 ]. Notably, FH from AMD patients carrying the risk polymorphism for AMD shows an impaired binding to mCRP and, therefore, its proinflammatory effects remain unrestrained [ 28 ]. In line with these findings, data demonstrates that mCRP is the more abundant form of CRP in human RPE-choroid [ 29 ], and that mCRP levels are elevated in individuals with the high-risk CFH genotype [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%